2012
DOI: 10.1111/j.1364-3703.2012.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene profiling in partially resistant and susceptible near‐isogenic tomatoes in response to late blight in the field

Abstract: In order to better understand resistance to Phytophthora infestans in tomato, we compared the global gene expression of the susceptible tomato, M82, with its more resistant near-isogenic line, 6-2 (IL6-2), under field conditions using a microarray with more than 12 800 tomato expressed sequence tags (ESTs). Because variance in the field was a major concern, we investigated the likelihood of false positives or false negatives and demonstrated that either probability was very low. The two isolines had indistingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…After pathogen infection, we noted a decrease in transcript abundance of genes associated with the production of ROS, which continued through the transition stage. A similar decline in ROS during the biotrophic stage was detected in a study investigating gene expression conducted in the field in the highly compatible P. infestans –tomato interaction ( US17 ‐M82; Cai et al ., ). This contrasts with the P. infestans ( US17 )–tomato interaction involving the partially resistant IL6‐2, where ROS were highly expressed as early as 36 hai (Cai et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After pathogen infection, we noted a decrease in transcript abundance of genes associated with the production of ROS, which continued through the transition stage. A similar decline in ROS during the biotrophic stage was detected in a study investigating gene expression conducted in the field in the highly compatible P. infestans –tomato interaction ( US17 ‐M82; Cai et al ., ). This contrasts with the P. infestans ( US17 )–tomato interaction involving the partially resistant IL6‐2, where ROS were highly expressed as early as 36 hai (Cai et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A similar decline in ROS during the biotrophic stage was detected in a study investigating gene expression conducted in the field in the highly compatible P. infestans –tomato interaction ( US17 ‐M82; Cai et al ., ). This contrasts with the P. infestans ( US17 )–tomato interaction involving the partially resistant IL6‐2, where ROS were highly expressed as early as 36 hai (Cai et al ., ). Recently, it has been shown that the cysteine protease effector HopN1 of the hemibiotrophic pathogen Pseudomonas syringae pv.…”
Section: Discussionmentioning
confidence: 97%
“…The identification of a large set of genes more highly expressed in one NIL versus another is not common. A comparison of resistant and susceptible NILs of tomato indicated that their transcriptomes were indistinguishable in non-inoculated lines, whereas several hundreds of DEGs were revealed after inoculation with Phytophthora infestans (Cai et al, 2013). Similarly, DEGs between NILs were identified only after inoculation of Fusarium graminearum in wheat (Schweiger et al, 2013) or in maize (Ye et al, 2013).…”
Section: The Prae1 Qrl Is Associated With Constitutive Expression Of mentioning
confidence: 99%
“…The P. infestans –tomato interaction can be highly compatible, partially compatible or incompatible, and these differences can be a consequence of both the plant genotype and whether or not the P. infestans strain is tomato specialized (Smart et al ., ). Importantly, it has been demonstrated previously that the P. infestans –tomato interaction is characterized by a prolonged biotrophic phase and a distinct necrotrophic phase at later stages of infection with tomato‐specialized isolates (Berg, ; Cai et al ., ; Smart et al ., ; Vega‐Sanchez et al ., ). We analysed the transcriptomes of the tomato‐specialized P. infestans isolate ( US‐11 ) and its host tomato (M82) in a highly compatible interaction using RNA sequencing (RNA‐Seq), in order to identify suites of co‐expressed genes that could be associated with each stage of the interaction and to infer regulated pathways from both the pathogen and host plant.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent necrotrophic phase is characterized by hyphal ramification and water soaking, followed by necrosis of the tissue (Grenville-Briggs et al, 2005). However, marked differences in the duration of both biotrophic and necrotrophic growth, depending on the host-P. infestans isolate interaction, have been reported previously (Berg, 1926;Cai et al, 2013;Smart et al, 2003;Vega-Sanchez et al, 2000). There is an extended period of biotrophy between tomato and certain tomato-specialized isolates of P. infestans, (Berg, 1926;Cai et al, 2013;Smart et al, 2003;Vega-Sanchez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%